Overview of bioactivity studies on marine natural products. Issue 1 (December 2021) - Zamani, N P; Rahman, L; Rosada, R L; Tirtama, W
Abstract: Marine natural products are sourced from marine biodiversity as natural raw materials for various commercial products. This study aims to review natural products of marine organisms and gap analysis for future research or challenges. A total of 109 references from 24 countries were collected. The analysis was carried out quantitatively and qualitatively. The bioactive compounds produced wereantioxidants, antibacterial, anticancer, antimicrobial, anti-fouling, antifungal, and anti-tumoral substances. Some marine organisms that can store chemical compounds through secondary metabolite processes are mangroves, seagrasses, macroalgae, microalgae, soft corals, molluscs, echinoderms, gastropods, cnidarians, sponges, fungi, and bacteria. Most of the papers only discuss the identification stage of the active compound, and some focus on product development. There are very few studies on prospects of commercialization and mass production. The problem to achieve mass production is due to the lack of interdisciplinary research collaboration. Future research challenges need to develop a transdisciplinary approach to study bioprospection research from upstream to downstream, starting from the potential identification of bioactive ingredients, product development, the availability of raw materials for mass production as well as commercialization and marketing.